Policies of global English tests: test-takers' perspectives on the IELTS retake policy. Issue 3 (3rd May 2016) - Hamid, M. Obaidul
Abstract : Globalized English proficiency tests such as the International English Language Testing System (IELTS) are increasingly playing the role of gatekeepers in a globalizing world. Although the use of the IELTS as a 'policy tool' for making decisions in the areas of study, work and migration impacts on test-takers' lives and life chances, not much is known about its own policy and policy logic. With the growing call for listening to test-takers' voices, specific policy aspects of the test have recently been scrutinized. This article seeks to contribute to this area by drawing on test-takers' perspectives on the IELTS retake policy and developing an understanding of how policies of global English tests are perceived, interpreted and given new meanings by its key stakeholders. Although the truth-value of the emic views of test-takers may be debated, their experiences and perceptions problematize the reliability claims of the testing agency by locating commercial motives at the center of their policy and thereby raising theoretical, professional and ethical questions.